1985
DOI: 10.1007/bf00251178
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing gain per effort by using clonal replicates in genetic tests

Abstract: Models for predicting cummulative genetic gain from recurrent selection applicable to predominantly outcrossing plant species are derived to include the effect of observations on clonal replicates (ramets) in addition to observations on individuals and family means. Such models are discussed with special reference to forest trees. The consequence of redistributing effort from individuals to ramets is investigated for several conditions with a fixed number of families and fixed total test size. Factors that aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 1 publication
1
23
0
1
Order By: Relevance
“…The effect of clonal testing was more important than the inclusion of the multigeneration relationship data set to the genetic evaluation by BLUP. This supports the benefits of clonal assessment in progeny testing for forest tree breeding programs described by other authors (e.g., Shaw and Hood 1985;Russell and LooDinkins 1993;Mullin and Park 1994;Danusevicius and Lindgren 2002;Isik et al 2003).…”
Section: Resultssupporting
confidence: 86%
“…The effect of clonal testing was more important than the inclusion of the multigeneration relationship data set to the genetic evaluation by BLUP. This supports the benefits of clonal assessment in progeny testing for forest tree breeding programs described by other authors (e.g., Shaw and Hood 1985;Russell and LooDinkins 1993;Mullin and Park 1994;Danusevicius and Lindgren 2002;Isik et al 2003).…”
Section: Resultssupporting
confidence: 86%
“…In addition, using clonal replicates in progeny tests can improve the accuracy of selection for additive genetic merit (Shaw and Hood 1985;Shelbourne 1991), and thus act to increase gain for both breeding and production populations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as discussed by KUMAR (2006), various simulation studies had indicated the advantages of cloning in the breeding population (SHAW and HOOD, 1985;JEFFERSON and WEAVER, 1997;ROSSVALL et al, 1998;DANUSEVICIUS and LINDGREN, 2002). These studies were followed by SHELBOURNE et al's (2007) empirical simulations.…”
Section: Influence and Experience From Other Programmesmentioning
confidence: 99%